The association between nicotine dependence and sleep quality in patients referred to a smoking cessation outpatient clinic: A cross-sectional study - Umran Ozden Sertcelik; Aysegul Karalezli (Tobacco Induced Diseases)
Introduction Nicotine addiction is one of the most common forms of dependence. It is shown to be associated with many chronic diseases that develop mostly through smoking. The association between sleep quality and smoking or nicotine addiction has not been clarified yet. This study aimed to investigate the association between nicotine addiction and sleep quality.